Determination of Amikacin in Different Pharmaceutical Formulations Using a Resonance Rayleigh Scattering Method with Pontamine Sky Blue - Han, Wenli; Qu, Fei; Shang, Jingchuan; Lu, Wei; Yang, Junqing; Ma, Qing (Current Pharmaceutical Analysis, 2014)
Amikacin (AMK) is a semisynthetic aminoglycoside antibiotic derived from kanamycin A that lacks a strong ultraviolet absorbing chromophore or fluorophore. Greatly enhanced resonance Rayleigh scattering (RRS) signals of AMK can be observed with a conventional fluorescence spectrophotometer when AMK interacts with pontamine sky blue (PSB) and forms an ion-association complex in weakly acidic buffer medium. Based on these characteristics, a sensitive assay for detecting AMK was developed. The maximum RRS peak was observed at 362 nm. The enhancement of the RRS signal was directly proportional to the AMK concentration in the range of 0–1.7 μg/ml, and its detection limit (3σ) was 3.0 ng/ml. The method showed a wide linear range and high sensitivity, and almost no interference could be observed from coexistent substances. In addition, this assay was performed in different pharmaceutical formulations of AMK with satisfactory results. Therefore, the proposed method is promising as an effective means for the determination of AMK.
Keywords: quantitative determination